Studi Deskriptif Proses Penggunaan Aplikasi Kesehatan Mental: Studi Kasus: Aplikasi Teduh - Navira Isni Nuraini,; Didik Setyawan,; Nang Among Budiadi, (Student Scientific Creativity Journal, 2024)
This research aims to explore public responses regarding the existence of mental health applications. This research was conducted using descriptive qualitative phenomenological methods. This research uses a phenomenological approach with data collection techniques using focus group discussions and interviews. The object of this research was students aged 16-22 years and who had experience with mental health. The data obtained came from 8 people in FGDs and 16 people in interviews with a trial period of 3-4 weeks. The results of the research show that the user interface has an effect on the user's perspective, application performance has an effect on the intention to use it continuously, emotional release has an effect on changes in individual behavior.